Desafios da agricultura familiar frente a agricultura do século XXI no município de Assis Chateaubriand - PR - Mandotti , Sônia Maria (2022)
The aim of this work was to understand the characteristics of Family Farming (FA) in the municipality of Assis Chateaubriand - PR, with the elaboration of its contextualization in the face of the XXI century and to describe the challenges of this segment in the municipality. Through questionnaires and interviews, data were collected from 35 subjects, 27 of whom were named family farmers, 4 members of the Association of Organic Producers of Assis Chateaubriand, and 4 local leaders. In addition, theoretical sources addressing the conceptions of Family Farming and sustainability were used. The data was submitted to quantitative analysis employing descriptive statistics, allowing the information to be organized in tables and figures. It can be seen that the spatial and temporal clipping reveals a Family Farming that has suffered the interference of agricultural modernization since the 1970s, and more recently with the implementation of technologies in the means of production. The fertile soils of the region contributed to the municipality being among the ten largest agricultural producers in Paraná, with emphasis on the production of commodities. This is even more relevant when we see that local family farming is focused on the production of agricultural commodities. The few family farmers who opted for organic production face problems in maintaining production due to the acquisition of agricultural inputs free of contaminants that fit the environmental criteria, the access to specific credit to the activity, and to ATER (Technical Assistance and Rural Extension) specialized in organic production. It is emphasized that organic agriculture is an alternative for strengthening family farmers, but the way it is promoted in the municipality of Assis Chateaubriand might be considered unsustainable.